Kajian Masyarakat Adat Rumbio dan Relevansinya Sebagai Sumber Nilai Dalam Pembelajaran IPS - Ahmal Ahmal; Piki Setri Pernantah (UIN Fatmawati Sukarno Bengkulu, 2021)
This research is motivated by the problem of forest destruction in Riau Province which often occurs for years due to human behavior. The environmental care attitude of the Kampar indigenous people towards the prohibited forest in Kenagarian Rumbio, Riau Province is one of the sources of the values of character education that cares for the environment that can be internalized to students. These social studies learning resources are sourced from local cultures that can form knowledge, attitudes and actions that seek to prevent forest destruction and take various actions for environmental conservation. The focus of this research is to identify the values of the environmental care character of the Kampar indigenous community towards the prohibited forest of the Kampar customary community and integrate it into social studies learning. This study uses a qualitative approach with ethnographic methods. The results showed that there were three things in the forest preservation of the prohibited communities of the Kampar custom society in Kenagarian Rumbio, namely; 1) view of the forest as part of the life of custom society; 2) the role of ninik mamak in customary communities in the form of rules and norms, prohibitions and myths, and then the role of nephews in the Pelopor Foundation, Rural Forestry Extension Center and Tourism Awareness Group or Pokdarwis; and 3) informal education system in building ecological awareness of prohibited forest to the younger generation. Then, it can be implemented the character value of environmental care for the indigenous people of Kampar towards the prohibited forest in Kenagarian Rumbio in social studies lessons to foster ecological awareness of the environment and forests.